Finite-time dissipative control for singular Markovian jump systems via quantizing approach. (February 2018) - Li, Shuiying; Ma, Yuechao
Abstract: This paper investigates the problem of finite-time dissipative control for a class of time-delayed singular Markovian jump systems (SMJSs) with time-varying transition rates by using a quantized approach. To begin with, sufficient conditions on singular stochastic finite-time admissible are obtained for the family of SMJS with time-varying transition rates. Following this, the results are extended to singular stochastic dissipative finite-time admissible of SMJS with time-varying transition rates. Then state feedback controllers are designed to ensure the singular stochastic finite-time admissible and the singular stochastic dissipative finite-time admissible of the underlying closed-loop SMJS in the forms of strict linear matrix inequalities (LMIs). Ultimately, numerical examples are used to indicate the correctness and effectiveness of the proposed methods.